Avaliação dos resíduos da construção civil (RCC) gerados no munício de Santa Maria - Piovezan Junior, Gilson Tadeu Amaral (2007)
The construction industry is considered one of the most important activities to economical and social development in Brazil; however it is producing negative effects on the environment due to high consumption of raw material, landscape modification and high amount of waste generation. According to results determined in Brazil, the average rate of C&D waste is 230-760 kg/person.year and international estimates range between 130-3000 kg/person.year. Santa Maria County has an urban population of 242.000 inhabitants and do not have a management system of C&D waste as stated on is Resolution N° 307 of the Nati onal Environmental Council of Brazil of July 5th of 2002. The aim of this work was to evaluate the real situation of C&D waste in Santa Maria. An inventory of transport companies was performed to estimate the amount of C&D waste generated in the county. The results show a generation of the 3,184 m³/month, that gives a rate of 189,46 kg/person.year. The C&D waste are being disposed in inappropriated places yielding environment and public health problems. The results demonstrate that the C&D waste rates are below the results noticed in prior studies. This study proposes actions for the development of an environment program for C&D waste management of Santa Maria County